A Phytochemical and Antibacterial Analysis of Echinacea Purpurea (L.) Moench Throughout Seasonal Development - Daley, Elizabeth (Université d'Ottawa / University of Ottawa, 2019)
Echinacea purpurea is consumed as a natural health product around the world. Due to the genus’ ethnobotanical relevance, the phytochemistry of Echinacea has been extensively studied, revealing a variety of bioactive metabolites including caffeic acid derivatives and alkylamides. Whereas seasonal trends in root chemistry have been established, trends in other plant parts are relatively understudied. Similarly, few studies have evaluated the effects of organic plant growth substances in field trials. With increased demand for organic products, industry is looking for alternative ways to optimize yields and medicinal properties. For this thesis, my first objective was to quantify the concentrations of E. purpurea’s secondary metabolites across organic treatments throughout the plant’s first growth year to determine optimal harvesting time and conditions in all parts of the plant. The second objective was to determine how seasonal variations affect its potential bioactivity through inhibition of Pseudomonas aeruginosa. Plants were grown in field plots treated with four different organic treatments: water (control), high cytokinin, low cytokinin, and fish oils; samples were collected biweekly from May-September. Dried plants were separated into major plant parts and were extracted exhaustively in 70% EtOH. Using high-pressure liquid chromatography (HPLC), concentrations of alkylamides and select caffeic acid derivatives were quantified in all samples and compared across plant part, developmental stage, and organic fertilizers. It was determined that while there were no major differences between treatments, phytochemical concentrations changed throughout the season in all plant parts; revealing that aerial parts of the plant also bioactive secondary metabolites and should not be excluded from future studies. Following this study, an MIC50 assay was used to test these extracts against P. aeruginosa PA14. It was noted that seasonality effects of phytochemistry were not consistent with bioactivity and that there were no significant differences between extract and carrier control. While the antibiotic activity of root extracts varied seasonally, the flower extract exhibited the most consistent antibiotic potential. The results presented in this thesis will not only aid in industry practices and yield optimization but, through filling knowledge gaps on seasonality and organic treatments in field trials, will increase the understanding of E. purpurea’s chemistry and related bioactivity, with implications on both the medicinal properties and eco-physiology of the species.
Keywords: Echinacea Purpurea; Phytochemistry